Women and gender a focus of the IPMS project in Ethiopia - Aregu, Lemlem (International Livestock Research Institute, 2011)
Lemlem Aregu explains how gender and the role of women are taken into account in the IPMS project at ILRI. She was speaking at the IPMS experience-sharing workshop on Market-Oriented Smallholder Development in Ethiopia, 2-3 June 2011 in Addis Ababa.